Think non-ethnic, but act ethnic: Perspectives from South Asian entrepreneurs - Mark McPherson (Journal of Entrepreneurship, Management and Innovation)
Literature pertaining to ethnic entrepreneurship assumes that religious-cultural and generational factors espouse the intention and ability of the entrepreneur towards business development. And by way of business growth and development, such entrepreneurs should breakout from their local ethnic customer base to service a wider non-ethnic customer base. In reality, many ethnic entrepreneurs lack the resources, the motivation, the ability and/or intention to do this. Consequently, the development and success of the business become hampered. To this end, working within a context of ethnic entrepreneurship, the aim of this paper is to examine the notion that entrepreneurial intention, ability and opportunity inform business growth, development and how the entrepreneur defines the success thereof. Addressing this, 48 semi-structured interviews and 11 comparative case studies were conducted with first- and second-generation South Asian Sikh, Hindu and Pakistani Muslim entrepreneurs within Greater London. A phenomenological paradigm was adopted, with key-words-in-context used to analyze data. Findings note there is no evidence of genuine breakout. Instead, what defines business development and growth is three approaches: (i) content to remain, (ii) forced to remain, and (iii) struggling to adjust. Hindered are attempts to increase the customer and market base beyond that of local clients. Additionally, differences and success between the two generations are reflective of sectorial location, intention, ability and skill-sets, rather than generational or cultural influences. Essentially, the paper presents an alternative view of how entrepreneurial intention, ability and opportunity facilitate or inhibit small business growth and success. However, given the sample-frame and, socio-economic environment within Greater London, findings may not be generalizable. In conclusion, debate pertaining to ethnic entrepreneurship needs to be re-examined; because placing emphasis on culture, religion, ethnicity and generation may be misleading researchers as to the true nature of business requirements, problems and support for ethnic entrepreneurs.